Azimuth resolution analysis in geosynchronous SAR with azimuth variance property. Issue 6 (1st March 2014) - Wu, Zhouting; Huang, Lijia; Hu, Donghui; Ding, Chibiao
Abstract : In geosynchronous synthetic aperture radar (GEO SAR), the azimuth FM rate drastically falls and comes close to the variation rate of the Doppler centroid, due to the higher altitude. The effect of the variation of the Doppler parameters becomes significant and affects the azimuth resolution results. A concise azimuth resolution expression is deduced from the azimuth ambiguity function which involves the azimuth variance property and third‐order range equation. It is more accurate for GEO SAR than the conventional expression. Meanwhile, the phenomenon where the traditional frequency algorithm becomes invalid is found. However, the time domain algorithm is still applicable when the azimuth FM rate approaches zero. Finally, the simulation results of the point targets at five typical areas verify the analysis.